The Crosstalk Between Osteodifferentiating Stem Cells and Endothelial Cells Promotes Angiogenesis and Bone Formation - Genova, Tullio; Petrillo, Sara; Zicola, Elisa; Roato, Ilaria; Ferracini, Riccardo; Tolosano, Emanuela; Altruda, Fiorella; Carossa, Stefano; Mussano, Federico; Munaron, Luca (Frontiers in Physiology, 2019)
A prominent therapeutic approach for bone regeneration involves the use of Mesenchymal Stem Cells (MSCs) to support bone repair. Only recently, has the synergistic crosstalk between osteodifferentiating stem cells and endothelial cells (ECs) gained the deserved consideration, shedding light on the role of angiogenesis for bone formation and healing. A deep understanding of the molecular basis underlying the mutual influence of MSCs and ECs in the osteogenic process may help improve greatly bone regeneration. Here, the authors demonstrated that osteodifferentiating MSCs co-cultured with ECs, promote angiogenesis and ECs recruitment. Moreover, through the use of 3D co-culture systems, we showed that ECs are in turn able to further stimulate the osteodifferentiation of MSCs, thus enhancing bone production. These findings highlighted the existence of a virtuous loop between MSCs and ECs that is central to the osteogenic process. Unravelling the molecular mechanisms governing the functional interaction MSCs and ECs holds great potential in the field of regenerative medicine.